Pendidikan Profesional Untuk Wartawan - Rusdiono Mukri (JURNAL KAJIAN ISLAM MODERN, 2019)
The research and writing of this paper is intended to provide input or suggestions to the management of press publishing in order to provide solutions to human resource quality problems in the field of journalism. Professional journalists hold firm journalistic ethics. Adherence to the code of conduct is one of the characteristics of professionalism, in addition to expertise, attachment and freedom. With the code of ethics guidelines, a journalist will not confuse facts and opinions in writing news; will not write slander, sadistic, and obscene news; will not "mortgage her freedom" by receiving an envelope; and only inform true or factual. In order to improve the competence and professionalism of journalists, starting in 2012, the Press Council held a competency test for journalists (UKW). That's why every journalist needs to improve his competence and professionalism in order to obtain a professional certificate as a journalist. The Indonesian Journalist Association organizes the Indonesian Journalism School (SI) to equip Indonesian journalists to have competence as a professional journalist. The development of the Indonesian Journalism School is done through two approaches: academic and empirical.